2004
DOI: 10.1021/bi034823n
|View full text |Cite
|
Sign up to set email alerts
|

IA3, an Aspartic Proteinase Inhibitor from Saccharomyces cerevisiae, Is Intrinsically Unstructured in Solution

Abstract: IA(3) is a highly specific and potent 68-amino acid endogenous inhibitor of yeast proteinase A (YprA), and X-ray crystallographic studies have shown that IA(3) binds to YprA as an alpha-helix [Li, M., Phylip, L. H., Lees, W. E., Winther, J. R., Dunn, B. M., Wlodawer, A., Kay, J., and Gustchina, A. (2000) Nat. Struct. Biol. 7, 113-117]. Surprisingly, only residues 2-32 of IA(3) are seen in the X-ray structure, and the remaining residues are believed to be disordered in the complex. We have used circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…To further understand loop stabilization upon peptide binding, we also acquired steady-state 1 H- 15 N heteronuclear NOE measurements, which offer information on motions [49, 50] and can be used to identify order induced binding or ordered conformations in partially folded ensembles. Typically, the value for the heteronuclear 15 N [ 1 H] NOE of folded residues is ~1–0.7, and the NOE for a flexible loop is <0.5.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand loop stabilization upon peptide binding, we also acquired steady-state 1 H- 15 N heteronuclear NOE measurements, which offer information on motions [49, 50] and can be used to identify order induced binding or ordered conformations in partially folded ensembles. Typically, the value for the heteronuclear 15 N [ 1 H] NOE of folded residues is ~1–0.7, and the NOE for a flexible loop is <0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, only residues 2-32 of IA 3 were seen in the X-ray structure, whereas the remaining residues are probably disordered in the complex . Recently, using CD and NMR spectroscopies it has been shown that IA 3 is unstructured in the absence of YprA (Green et al, 2004). The unfolded IA 3 samples used for NMR analyses were active and inhibited YprA with an inhibition constant (K i ) of 1.7 nM.…”
Section: Caldesmon-calmodulin Interactionmentioning
confidence: 99%
“…The unfolded IA 3 samples used for NMR analyses were active and inhibited YprA with an inhibition constant (K i ) of 1.7 nM. The addition of YprA led to a large spectral transition in IA 3 (Green et al, 2004). Thus, IA 3 is another example of an intrinsically disordered protein that folds when it recognizes its binding partner protein or that is stabilized in an otherwise transient conformation upon binding to its partner.…”
Section: Caldesmon-calmodulin Interactionmentioning
confidence: 99%
“…By itself, free IA 3 is essentially unstructured (5), but, upon contact with its target proteinase, the polypeptide operates as an inhibitor through an unprecedented mechanism (3,4). Residues 2-32 become ordered and adopt an almost perfect amphipathic helical conformation occupying the active site of the enzyme (3,4).…”
mentioning
confidence: 99%